PARADIGMA KEBEBASAN BERPENDAPAT: ANONIMITAS, BUDAYA PARTISIPASI, DAN DOMINASI SUBYEKTIFITAS PENGETAHUAN DI RUANG DIGITAL - Wardhana, Arya Wijaya Pramodha; Tiara, Ayunda Trisna Ludi; Sugihartati, Rahma; Asmiyanto, Taufik; Wibowo, Muhamad Prabu (Jurnal Abdi Insani, 2024)
Social networking is a platform where various users with different information needs, and access purposes come together. With this condition, to ensure the security and privacy comfort of users, Anonymity has emerged as a "minimal facility" to secure personal information when users are networking. However, as the characteristics of users evolve over time, there is a shift in usage preferences and compliance with regulations and ethics in social networking spaces. This also leads to the simultaneous growth of malfunctions in Anonymity that lead to unethical actions and even criminal activities. With various issues arising, this paper aims to explore the shift in usage patterns and user characteristics contributing to the emergence of Anonymity deviations in the digital space, using the concepts of digital culture and ethics. Using a literature review method, this research aims to form a comprehensive understanding of the use of Anonymity in the digital space. This research employs a descriptive qualitative approach with a constructivist paradigm, focusing on collecting conceptual and theoretical data as well as supporting data related to freedom of expression, anonymity, participatory culture, and the dominance of subjective knowledge in the digital space over a span of 15 years (2008-2023). The study's results are expected to provide recommendations acceptable to all stakeholders and serve as a basis for further discussion in the same context in the future. The research concludes that Anonymity in the digital space presents challenges related to intellectual property rights, an increase in cybercrime cases, and uncontrolled access to controversial content such as pornography, making government regulation difficult due to technical constraints.